Estudo da divisão nuclear em Rhinosporidium seeberi utilizando marcadores específicos de fluorescência avaliados por microscopia confocal - Darly Gomes Soares (2015)
Rhinosporidium seeberi is an uncultivated Ichthyosporean causing rhinosporidiosis in animals, including humans. For being resistant to culture, its life cycle can be studied only in fresh or formalin fixed tissues. For this reason, its taxonomic position has been discussed for more than 100 years. Recent phylogenetic molecular studies showed that the R. seeberi is located in a new group of fish, amphibians and other animals pathogens, called Mesomycetozoa. Very little is known about R. seeberi life cycle and much less about its nuclear cycle in the host with rhinosporidiosis. Recent studies have shown that this pathogen has synchronized nuclear division without cytokinesis. Therefore, to study R. seeberi nuclear cycle and validate previous studies, we used confocal microscopy to investigate R. seeberi nuclear behavior in formalin fixed tissues stained with DAPI and phalloidin. We report that R. seeberi juvenile sporangia showed DAPI stained nuclei (5 to 7 ìm) and, as the cell cycle progresses, the nuclei synchronously divided without cytokinesis. Intermediary sporangia displayed numerous 3 to 4 ìm DAPI stained nuclei at different mitotic stages and a thick inner layer that strongly retain the conjugates of phalloidin. Mature sporangia displayed multiple 5 to 12 ìm cell walled endospores each holding 2 to 4 ìm in diameter nucleus. The conjugate of phalloidin did not bind to the inner layers of mature sporangia or endospores. The development of a germinative zone in the inner layer of mature sporangia containing hundreds of DAPI stained nuclei was also confirmed. This study established that during R. sebeeri life cycle synchronous nuclear divisions take place resulting in the formation of multiple nuclei. Cytokinesis is one time event and occurs after the formation of thousands of nuclei just before mature sporangia formation.